Alinlangan (Doubt) - Tianzon, Ludy Anne C. 1993- (Quezon City College of Mass Communication, University of the Philippines Diliman, 2016)
"Alinlangan is an experimental film about a woman who has weight issues. She thinks that women in the society should have an ideal body and image. With that, she is under pressure with self-perception. She later on proves to herself that it was all but a mental challenge."
Vita.
Thesis (A.B. Film)--University of the Philippines Diliman